Effect of Selected Leguminous Cover Crop Species on the Productivity of Coconut Cultivated in Reddish Brown Latosolic Soils in Sri Lanka - Senarathne, S.H.S.; Udumann, S. S. (International Coconut Community Journal, 2021)
This study was conducted for six years to assess the effects of two widely grown cover crops Gliricidia sepium (T1) and Puereria phasioloides (T2) on coconut yields and soil characteristics. Experiments were carried out on coconuts planted in Reddish Brown Latosolic soils located in the low country intermediate zone-IL1 of Sri Lanka. Results showed that treatments 1 and 2 were significantly (p≤0.05) effective over the control treatment (no cover crop) in suppressing weed biomass. Soil samples were collected and analyzed for physical, chemical and biological properties. Results showed that soils where G. sepium and P. phasioloides were grown were superior in most of the properties compared to the control. Soils under P. phasioloides showed significantly higher moisture contents compared to G. sepium and control treatments. Significant increases on soil properties were likewise observed in G. sepium and P. phasioloides plots: nitrogen (by 77% and 76 %), organic carbon content (by 86% and 148%), soil microbial activity (by 52% and 73%), respectively. On the other hand, soil bulk densities were reduced significantly by 20% and 27% under G. sepium and P. phasioloides, respectively. There was no significant increase observed on available P but P content improved with the establishment of cover crops. Significant increases in mean annual nut yields were observed during the 4th, 5th, and 6th years after cover crops establishment. Nut yields were found to increase with G. sepium and P. phasioloides by 46% and 58%, respectively when compared to that of control treatment plots.